Resistance of rice cultivars and lines to the lesser cornstalk borer - Ferreira, Evane; Martins, José Francisco da Silva; Zimmermann, Francisco José Pfeilsticker (Pesquisa Agropecuaria Brasileira, 2014)
The preliminary study to verify the possibility of obtaining resistance in rice to the lesser cornstalk borer Elasmopalpus lignosellus (Lepidoptera phycitidae) (Zeller 1848) has indicated difference between the reaction of cultivars and lines to damage of insect, in natural conditions of infestation, until the maximum period of 162 days. The line BKN-6652-249-1-1, was the most resistant and has shown 13,9% of dead plants, while the cultivar Catetão was the most damaged, with 32,6% of dead plants. It was observed that the highest concentration of the damages caused by the lesser cornstalk borer, appeared in the two months following the emergence of the plants (during the vegetative phase), existing indications that one of the reactions of the rice plants to the insect is probably a resistance of the "tolerance" type, associated with the tillering capacity of the plants after the infestation.